Efficiency of Effluent Treatment Plants and Threat to Human Health and Aquatic Environment in Bangladesh - Akhtar, Parul; Ahmed, Yunus; Islam, Faridul; Alam, Khorshed; Mary, Meherunnesa; Islam, Md. Zahidul; H. Bhuiyan, M. Mosharef; Yaakob, Zahira (Asian Journal of Chemistry, 2015)
Bangladesh is a low-lying riverine country. It has about 230 small and large rivers and a large portion of the country’s 140 million people depends on them for a living and for transportation. Most of the rivers and canals are becoming increasingly polluted from industrial wastewater dumped by factories, many of them in the textile, leather tanneries, pulp and paper, pharmaceutical, engineering workshops as well as chemicals and pesticide industry. Nonetheless, the wastewaters discharged from them are harshly ruinous to the environment, contains various kinds of contaminant which contaminate the water bodies, aquatic sediments, soil and ultimately incorporated into the muscles of fish, vegetables, etc. Many researchers have tried to find out the percentages of a contaminant available in different rivers and their effect on agriculture, environment and human health. Some of their research on discharging industrial wastewater quality, but none of them find out, the effectiveness of industrial effluent treatment plants. The emphasis of this research is to give a detail indication of the discharging contaminants from the five experimental industries and their effluent treatment plants (ETP). Most of our experimental industrial effluent treatment plants were able to reduce their physical parameter (BOD, COD, TSS, TDS, TS, turbidity, pH and EC) in moderate stages and two or three industry effluents were below the standard discharge limit prescribed by the Environmental Protection Agency (EPA), Bangladesh and their effluents were unsuitable for discharging into water bodies, but these are not fulfilled the US EPA guideline ranges. Whereas most of our experimental industries effluent treatment plants reduce small or less portions of metal content from their effluent which were not follow the EPA, Bangladesh and US EPA guideline ranges. They discharge their effluents into water bodies because of the lacking of a very efficient and economic treatment system.